Peran Pesantren dalam Mencegah Fundamentalisme-Radikalisme Agama: (Studi Kualitatif di Pesantren Nurul Ummah Desa Kembang Belor Kecamatan Pacet Kabupaten Mojokerto) - Laksono, Puji (Asketik: Jurnal Agama dan Perubahan Sosial, 2017)
Religious fundamentalism that leads to the action of religious radicalism becomes a common event that must be prevented. The religion which should be the source of love, peace, and salvation in human life is used as an instrument of abomination. This can be seen from the recent events of global terrorism acts today. This research has a theme about the role of Pesantren Nurul Ummah in preventing religious fundamentalism-radicalism which is a form of acts of terrorism. The purpose of this research is to know how the role of Pesantren Nurul Ummah in preventing religious fundamentalism-radicalism in the form of acts of terrorism. This research was conducted on foreign students at Pesantren Nurul Ummah, Kembang Belor, Pacet, and Mojokerto. The method used is qualitative The theory used is the Social Construction theory of Peter L. Berger and Thomas Luckmann. Data were collected through direct observation and in-depth interviews. The validity of the data was done by using triangulation. The results of this study indicate that the root problem of religious fundamentalism that led to the action of religious radicalism, can be seen from the aspect of a shallow religious understanding. The teachings of Islam contained in the Qur’an and Hadith in their understanding are not adapted to the social context. The role of pesantren in preventing religious fundamentalism radicalism, namely by playing the three functions. Among other religious functions, by giving an understanding of the text of the Qur’an and Hadith by its context, which is called asbab al-nuzul or asbab al-wurud. Then the function of education is by inculcating social values, such as the value of nationalism and pluralism. And the last is the social function, namely to equip students with social activities related to society.